Flying swords of Dragon Gate [videorecording (DVD)] - Tsui, Hark, 1950-; Li, Jet, 1963-; Zhou, Xun, 1974-; Chen, Kun, 1976- (Indomina, 2012)
A freedom fighter opposes corrupt eunuchs who hold power during China's Ming dynasty.